Individualism in the African Novel: A Heuristic Paradigm. - Anyadike, Chima (Obafemi Awolowo University, 2014)
In this study, patterns formed by highly individualistic characters in the African novel are investigated. It is hoped that firstly, this will throw some light on the problem of how the same societies that need strong individualistic characters for change and development, at the same time need to place certain limits on individualism if they are to muster adequate collective response to problems like colonialism, racism and corruption which cannot be eliminated by lone acts of courage. Secondly, the study also suggests an important dimension in the criteria for the criticism and evaluation of character in the African novel. Lucien Goldmann's formulation regarding the relationship between the themes and forms of literary texts and the moments of social and historical consciousness provide in part the methodological basis of analysis; however, Fanon's analyses of the moments of the colonized consciousness are also significantly relied upon.